The Binding Power of Teraupetic Agreements Reviewed from Health Law - Fadhillah, Farhan; Sudirman, Sudirman; Hamzah, Ismi Fadjriah (Postgraduate Program in Law, Universitas Pattimura, 2025)
Introduction: The enactment of Law Number 17 of 2023 concerning Health has brought a paradigm shift in the arrangement of therapeutic agreements between health workers and patients.Purposes of the Research: This study aims to analyze the binding power of therapeutic agreements by focusing on the legal position of the exoneration clause in informed consent and examining the form of settlement for patient losses.Methods of the Research: Using normative legal research methods with Statute approach and conceptual approach.Results Main Findings of the Research: This study reveals that therapeutic agreements have binding power based on the principle of adequate informed consent. However, the exoneration clause in informed consent faces stricter legal restrictions based on Law Number 17 of 2023, especially related to the expanded responsibility of hospitals. The research concludes that the binding power of therapeutic agreements must be balanced with the protection of patients' rights, and effective dispute resolution mechanisms are needed to ensure fairness for all parties.